Neuroinflammation underlies the development of social stress induced cognitive deficit in male sickle cell mice - S’Dravious A. DeVeaux; S’Dravious A. DeVeaux; Sofiya Vyshnya; Sofiya Vyshnya; Katherine Propsom; Oluwabukola T. Gbotosho; Asem S. Singh; Robert Z. Horning; Mihika Sharma; Anil G. Jegga; Liang Niu; Edward A. Botchwey; et al. (Experimental Biology and Medicine)
Cognitive deficit is a debilitating complication of sickle cell disease (SCD), with a multifactorial etiopathogenesis. Here we show that neuroinflammation and dysregulation in lipidomics and transcriptomics profiles are major underlying mechanisms of social stress-induced cognitive deficit in SCD. Male Townes sickle cell (SS) mice and controls (AA) were exposed to social stress using the repeat social defeat (RSD) paradigm concurrently with or without treatment with minocycline. Mice were tested for cognitive deficit using novel object recognition and fear conditioning tests. SS mice exposed to RSD without treatment had worse performance on cognitive tests compared to SS mice exposed to RSD with treatment or to AA controls, irrespective of their RSD or treatment disposition. Additionally, compared to SS mice exposed to RSD with treatment, SS mice exposed to RSD without treatment had significantly more cellular evidence of neuroinflammation coupled with a significant shift in the differentiation of neural progenitor cells towards astrogliogenesis. Additionally, brain tissue from SS mice exposed to RSD was significantly enriched for genes associated with blood-brain barrier dysfunction, neuron excitotoxicity, inflammation, and significant dysregulation in sphingolipids important to neuronal cell processes. We demonstrate in this study that social stress induces cognitive deficit in SS mice, concurrently with neuroinflammation and lipid dysregulation.